THE BUSINESS ANALYSIS OF TILAPIA AND TILAPIA MIXED COMMON CARP FLOATING CAGES AT TOBA LAKE IN KELURAHAN HARANGGAOL HARANGGAOL HORISON SUB DISTRICT SIMALUNGUN REGENCY NOTRH SUMATERA UTARA - Ningsih Agresia Hutagalung; Hendrik '; Darwis ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This study was conducted on 26 January to February 9 2016 in the Kelurahan Haranggaol Haranggaol Horison sub district Simalungun regency north sumatera province. The purpose of the study was to determine and profit tilapia and tilapia mixed common carp and tilapia floating cage tilapia and business, know tilapia mixed common carp in floating cage in the review of several criteria investation like FRR, RCR, PPC. The method used in this research is a case study. Based on the results obtained by comparasion of investment and business profit amounted 634.895.000 milion rupiah tilapia and tilapia mixedc ommon carp 704.395.000 milion rupiah. Based on investment criteria for tilapia is FRR 94 %, RCR 1.9 and PPC Years. As for tilapia mixed common carp are FRR 197 % and PPC 3.14 % and RCR 0,5 Years.Keywords : Analysis, Tilapia, Common carp, floating, Lake Toba